2016
DOI: 10.1088/1742-5468/2016/06/063401
|View full text |Cite
|
Sign up to set email alerts
|

The scaling of the minimum sum of edge lengths in uniformly random trees

Abstract: Abstract. The minimum linear arrangement problem on a network consists of finding the minimum sum of edge lengths that can be achieved when the vertices are arranged linearly. Although there are algorithms to solve this problem on trees in polynomial time, they have remained theoretical and have not been implemented in practical contexts to our knowledge. Here we use one of those algorithms to investigate the growth of this sum as a function of the size of the tree in uniformly random trees. We show that this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Another reason to not find anti-DDm in linear trees is that DDm may not be acting only at the level of the ordering of the words of the sentence but also at the level of the tree structures. The fact that D min , the minimum value of D for a given tree, is minimized by linear trees (Ferrer-i-Cancho, 2013), where D min = n − 1, and maximized by star trees (Esteban, Ferrer-i-Cancho, & Gómez-Rodríguez, 2016), where D min = n 2 − n mod 2 4 , suggests that DDm could be favouring the choice of linear trees to ease the optimization problem.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason to not find anti-DDm in linear trees is that DDm may not be acting only at the level of the ordering of the words of the sentence but also at the level of the tree structures. The fact that D min , the minimum value of D for a given tree, is minimized by linear trees (Ferrer-i-Cancho, 2013), where D min = n − 1, and maximized by star trees (Esteban, Ferrer-i-Cancho, & Gómez-Rodríguez, 2016), where D min = n 2 − n mod 2 4 , suggests that DDm could be favouring the choice of linear trees to ease the optimization problem.…”
Section: Discussionmentioning
confidence: 99%
“…We have seen above that k 2 is a fundamental structural property of a tree: it determines |Q|. As k 2 determines the range of variation of |Q|, k 2 also determines the solution to the minimum linear arrangement problem: the solution is minimum for linear trees and maximum for star trees [29]. k 2 is a measure of the hubiness of a tree [25] and we have seen that its range of variation is…”
Section: A Hubiness Coefficientmentioning
confidence: 99%
“…Suppose that the vertices of a linear tree with n ≥ 2 are labelled following a depth-first traversal from one of the leaves. This is equivalent to labelling vertices according to their position in a minimum linear arrangement [29]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We pay further attention to the particular case of trees given their interest for research on edge lengths, e.g., [ V rla [D 2 ] becomes an increasing linear function of k 2 when n is also constant (recall 33)). In trees where n is given, it has been shown that [11]…”
Section: Uniformly Random Labelled Treesmentioning
confidence: 99%